DESIGN RESEARCH OF SPATIAL THINKING AND NUMBER SENSE IN CHILDREN 5-6 YEARS OLD - Rooselyna Ekawati, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2008)
Abstract : Spatial thinking is one of the way to help children understand more about number sense.  In this design research, I observe the relation between the spatial thinking and emergence number sense. I look at children will use their spatial configuration of objects and determine the amount of it without counting. It will help children with low ability in number sense understand more the numbers through spatial thinking.